Social media use for work during non-work hours and turnover intention: the mediating role of burnout and the moderating role of resilience - Fang, Zhenbang; Bao, Yuanjie; Hua, Min (Frontiers in Psychology, 2024)
Introduction This study uses survey data from 504 Chinese teachers to investigate the relationship between social media use for work during non-work hours (SMUNW) and turnover intention, focusing on the mediating role of burnout and the moderating role of resilience in this relationship. Methods In November 2023, online survey links were sent to 529 teachers from Shandong Province, China, asking them to report their perceptions of SMUNW, burnout, resilience, and turnover intention. A sample of 504 valid responses was obtained. The analysis was performed using SPSS 26.0 and Hayes’ PROCESS MACRO for SPSS for testing the hypotheses. Results The results revealed that burnout acts as a mediator in the relationship between SMUNW and turnover intention. In addition, resilience moderated the relationship between SMUNW and burnout such that when resilience was higher, the relationship between SMUNW and burnout was alleviated. Moreover, resilience moderated the indirect relationship between SMUNW and turnover intention through burnout such that when resilience was higher, the indirect relationship was alleviated. Discussion The results of this study indicate that SMUNW is related to turnover intention through the mediating role of burnout. Furthermore, resilience moderates the influence of SMUNW on burnout and thus weakens the influence of SMUNW on turnover intention through burnout. This study expands our knowledge of the nuanced influence mechanisms of social media use in the context of increasing technostress among public employees. Practically, it suggests that managers should pay due attention to the impairments brought about by social media use, especially from the perspectives of preventing burnout and fostering resilience.